Revision of the genus Setosella (Bryozoa: Cheilostomata) with description of new species from deep-waters and submarine caves of the Mediterranean Sea - Rosso, A.; Martino, E. Di; Gerovasileiou, V. (Zootaxa, 2020)
The genus Setosella included to date six species. After revision, only four of these species were retained, i.e. S. vulnerata, S. cavernicola, S. folini and S. spiralis. The remaining two species were tentatively placed in Woodipora, W.? antilleana n. comb., and Andreella,  A.? fragilis n. comb. On the other hand, scanning electron microscopy examination of Mediterranean material, revealed the presence of three new species previously included in species complexes: S. cyclopensis n. sp. from the open-shelf, S. rossanae n. sp. from submarine caves, and S. alfioi n. sp. from deep-waters. The diagnosis of the genus was amended to include the occurrence of kenozooids in S. cyclopensis n. sp. and S. cavernicola, and of free-living ring-shaped and scorpioid colonies in S. folini and S. alfioi n. sp. All the seven species now in Setosella have present-day representatives; the geographic distribution of the genus is restricted to the NE Atlantic and adjacent seas; its stratigrafic distribution is rejuvenated to the late Tortonian-early Messinian of southern Italy and insular Greece, with only three species occasionally and discontinuously reported. All species are able to produce numerous, subsequent intramural buds and morphological differences seem to be consistently associated with exploitation of particular habitats and substrata.